Association of SARS-CoV-2 Serology Test Result and COVID-19 Vaccination in Adults: A Multisite Cohort Study - Glanz, Jason M.; Palmer-Toy, Darryl E.; Narwaney, Komal J.; Barrow, Jennifer C.; Bruxvoort, Katia J.; Kraus, Courtney R.; Lyons, Jason A.; Binswanger, Ingrid A. (AJPM Focus, 2025)
•SARS-CoV-2 serology test results influenced COVID-19 vaccination behavior.•A negative test result was associated with increased receipt of COVID-19 vaccination.•Perceived susceptibility to COVID-19 infection influences vaccination behavior.•SARS-CoV-2 serology test results appear to cause risk compensation.•Future research could explore using perceived susceptibility to boost vaccine uptake. Although the utility of SARS-CoV-2 serology testing is limited, individuals may have used serology test results to inform COVID-19 vaccination decisions during the pandemic. Serology test results may have changed individuals’ perceived susceptibility to SARS-CoV2 infection, leading to risk compensation behavior. Understanding how serology results as a measure of perceived susceptibility influence COVID-19 vaccination decisions could inform future interventions to increase adult vaccine acceptance. This study examined the association between SARS-CoV-2 serology (antibody) test results and COVID-19 vaccination uptake. This retrospective cohort study included adults who received ≥1 serology test between January 1, 2021, and February 28, 2023. The date of the first serology test represented Day 0, and vaccination uptake was followed for 30 days. Individuals could have multiple serology tests, and person-time follow-up was enumerated across tests. The main exposure was the SARS-CoV-2 serology test result. Receipt of COVID-19 vaccination (BNT162b2 or mRNA-1273) was analyzed using Cox proportional hazards regression, controlling for age, sex, race/ethnicity, tobacco use, and comorbidities. Within a cohort of 28,610 adults, there were 28,820 serology test results. Approximately 38% (n=10,802) of the cohort had at least 1 positive serology result. Among negative tests, the COVID-19 vaccination rate was 1,489 per 1,000 person-years of follow-up; among positive tests, the rate was 829 vaccinations per 1,000 person-years. A negative serology test result was positively associated with COVID-19 vaccination (adjusted hazard ratio=1.58; 95% CI=1.45, 1.72). SARS-CoV-2 serology results appear to influence vaccination behavior. Future interventions could target perceived illness susceptibility to increase vaccine acceptance.